Analysis of Customer’s Decision to Choose Sharia Banking in Surakarta - Sudarwati Sudarwati; Burhanuddin Ahmad Yani (Journal of Islamic Economic Laws, 2021)
This study aims at determining the influence of the profit-sharing system, security of funds, facilities and services toward Customer's decision to choose sharia banking in Surakarta. The research employs a method survey; it analyzes the Customer's decision to choose sharia banking. The researcher collects the data from the respondents through a questionnaire. The sample is taken by purposive random sampling. 100 customers come from 10 sharia banking in Surakarta. To test the hypothesis, the researcher uses multiple regression analysis, t-test, F test, and determinant coefficient by using SPSS. The finding of the research is that there is significant influence among variable profit-sharing system (X1), the security of funds (X2), facilities (X3), and service (X4) toward Customer's decision to choose sharia banking (Y). However, there is one significant influence. It is a profit-sharing system toward Customer's decision to choose sharia banking. The four variables; profit-sharing system, the security of funds, facilities, and services toward Customer's decision to choose sharia banking is 46.50%. At the same time, the rest is about 53.50 %, derived from another variable which is out of research.